Measuring The Quality of Learning Services in Relation to Students’ Loyalty Towards Learning Quality The Teacher Profession Education Program - Arif Julianto Sri Nugroho; Hersulastuti; Purwo Haryono; Tasari; Tukiyo; DB Putut Setiyadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2025)
This study aims to test the model of whether there is a direct influence of academic and non-academic service quality on loyalty through student satisfaction as a mediating variable of Teacher Profession Program students in Widya Dharma University (PPG Unwidha). Service quality is measured using Service Quality. The research design uses a multivariate quantitative method. The hypothesis is formulated using a test of the influence of independent variables and the influence of intervening variables. The research population is all Teacher Profession Education (PPG) students of Unwidha who have received learning services. The sampling technique for respondents is through purposive sampling of 120 PPG students in the Faculty of Teacher Training and Education of Unwidha. Confirmation of the quality of higher education services consisting: (a) learning structure, in the form of physical learning facilities, the ability of lecturers and educational staff involved, (b) process, including all academic administration activities, the quality of mid-semester exam activities, the quality of final exam activities, the quality of practicums and the concern of educational staff for problems that arise in students (c) learning outcomes, including student evaluation of the benefits of the learning model applied by lecturers to students. The test results obtained the conclusion that the academic service quality dimension has a dominant influence and there is an influence of intervening variables on student loyalty. This finding spurs the PPG program at Unwidha to continue to improve service quality. Increasing the quality of learning services will lead to the creation of competitive advantage and loyalty to the Unwidha PPG institution in the future.